WORKSHOP KOMUNIKASI PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN RAMAH LINGKUNGAN - Yuni Tresnawati; Sri Mulyati Sari Nasution (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
This study and community service program (PkM) analyze the impact of implementing a Green Marketing Communication (GMC) workshop on increasing environmental knowledge and promoting eco-friendly purchase decisions among Generation Z. The participants, students from SMKN 49 North Jakarta, represent a critical consumer group known for high environmental awareness but also high skepticism towards sustainability claims (greenwashing). The method employed a participatory approach through training, production and marketing simulations, and educational campaigns. The results indicate that the structured, practice-based workshop, particularly focusing on Green Promotion, was effective in significantly enhancing purchase intention and green buying behavior. The program successfully equipped students with an in-depth understanding of sustainable marketing and the practical skills to design persuasive and credible eco-friendly messages. The outputs include a structured green marketing education module and this scientific publication manuscript. This finding contributes to the understanding of how educational interventions can bridge the attitude-behavior gap in young consumers, fostering a more responsible consumption culture